Traumatic pediatric buccal fat pad herniation: A report of two cases - Divya Sharma; Jaspreet Kaur Deo; Akanshya Loshali; Pravesh Nath Mehra (Wolters Kluwer Medknow Publications, 2024)
The buccal fat pad (BFP) is a specialized encapsulated adipose tissue, located intimately between the buccinator muscle and oral mucous membrane. A small perforation of buccinator muscle can lead to herniation of BFP into the oral cavity, which can be readily mistaken with a pathological entity. In general, the size of herniated BFP is larger than the perforation. The treatment options for BFP are excision or repositioning in its anatomical position if noticed early. This article reports two such cases presenting with herniation of the BFP, following trauma to buccal mucosa and its surgical management.